Adherence to the Spanish dietary guidelines and its association with obesity in the European Prospective Investigation into Cancer and Nutrition (EPIC)-Granada study. Issue 11 (24th April 2014) - Molina-Montes, Esther; Uzhova, Irina; Molina-Portillo, Elena; Huerta, José-María; Buckland, Genevieve; Amiano, Pilar; Menéndez, Virginia; Barricarte, Aurelio; González, Carlos A; Sánchez, María-José
Abstract: Objective: Dietary guidelines are intended to prevent chronic diseases and obesity. The aim of the present study was to develop a diet quality index based on the Spanish Food Pyramid (SFP) and to further explore its association with obesity in the European Prospective Investigation into Cancer and Nutrition (EPIC)-Granada study. Design: Cross–sectional study. The SFP score considered recommendations given for twelve food groups, and for physical activity and alcohol consumption. Obesity was defined as BMI over 30 kg/m 2 and abdominal obesity as waist circumference larger than 102 cm (men) and 88 cm (women). Logistic regression was conducted to estimate odds ratios of obesity by quintiles and by 10-point increment in adherence to the score, controlling for potential confounders. Setting: EPIC-Granada study. Subjects: Participants ( n 6717) aged 35–69 years (77 % women). Results: A 10-point increase in adherence to the SFP score was associated with a 14 % (OR=0·86; 95 % CI 0·79, 0·94) lower odds of obesity in men ( P interaction by sex=0·02). The odds of abdominal obesity decreased globally by 12 % (OR=0·88; 95 % CI 0·84, 0·93) per 10-point increase in adherence to this score. The effect of higher adherence to the score on abdominal obesity was stronger in physically inactive men and women (ORper 10-point increase =0·79; 95 % CI 0·68, 0·92 and ORper 10-point increase =0·89; 95 % CI 0·84, 0·95, respectively). Conclusions: These findings support that the Spanish dietary guidelines might be an effective tool for obesity prevention. However, prospective studies investigating this association are warranted.